Penerapan Pembelajaran CIRC (Cooperative, Integrated, Reading, And Composition) Berbasis Kurikulum Merdeka Dalam Meningkatkan Hasil Belajar Sosiologi Siswa Kelas X SMA Negeri 13 Kabupaten Sinjai - Firdaus Firdaus; Jamaluddin Arifin (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
The role of the teacher as an instructor needs to shift to become a facilitator or guide in learning. One learning model that can facilitate this is Cooperative Integrated Reading and Composition (CIRC) so that student learning outcomes can improve. This research uses a type of classroom action research, which consists of two cycles. This research data was collected using observation sheets and student learning outcomes tests. The collected data was then analyzed quantitatively and qualitatively. The results of this research show that the application of CIRC (Cooperative, Integrated, Reading, And Composition) learning based on the Independent Curriculum can improve the learning outcomes of Class X students at SMA Negeri 13 Sinjai Regency and there is a significant change in students' attitudes towards learning. Thus, the findings of this research have an important contribution for students, teachers and educational practitioners to apply the Independent Curriculum-based CIRC (Cooperative, Integrated, Reading, And Composition) model in the sociological learning process at the high school education level.